Hepatokines and Adipokines in Metabolic Syndrome - Mukhuty, Alpana; Mondal, Samim Ali; Mukhopadhyay, Satinath (Annals of the National Academy of Medical Sciences (India), 2023)
Hepatokines and adipokines are secretory proteins derived from hepatocytes and adipocytes, respectively. These proteins play a main role in the pathogenesis of metabolic syndrome (MetS), characterized by obesity, dysglycemia, insulin resistance, dyslipidemia, and hypertension. Adipose tissue and liver are important endocrine organs because they regulate metabolic homeostasis as well as inflammation because they secrete adipokines and hepatokines, respectively. These adipokines and hepatokines communicate their action through different autocrine, paracrine and endocrine pathways. Liver regulates systemic homeostasis and also glucose and lipid metabolism through hepatokines. Dysregulation of hepatokines can lead to progression toward MetS, type 2 diabetes (T2D), inflammation, hypertension, and other diseases. Obesity is now a worldwide epidemic. Increasing cases of obesity and obesity-associated metabolic syndrome has brought the focus on understanding the biology of adipocytes and the mechanisms occurring in adipose tissue of obese individuals. A lot of facts are now available on adipose tissue as well. Adipose tissue is now given the status of an endocrine organ. Recent evidence indicates that obesity contributes to systemic metabolic dysfunction. Adipose tissue plays a significant role in systemic metabolism by communicating with other central and peripheral organs via the production and secretion of a group of proteins known as adipokines. Adipokine levels regulate metabolic state of our body and are potent enough to have a direct impact upon energy homeostasis and systemic metabolism. Dysregulation of adipokines contribute to obesity, T2D, hypertension and several other pathological changes in various organs. This makes characterization of hepatokines and adipokines extremely important to understand the pathogenesis of MetS. Hepatokines such as fetuin-A and leukocyte cell-derived chemotaxin 2, and adipokines such as resistin, leptin, TNF-α, and adiponectin are some of the most studied proteins and they can modulate the manifestations of MetS. Detailed insight into the function and mechanism of these adipokines and hepatokines in the pathogenesis of MetS can show the path for devising better preventative and therapeutic strategies against this present-day pandemic.
Keywords: metabolic syndrome; hepatokine; adipokine; type 2 diabetes; obesity; hypertension